2022
DOI: 10.3390/healthcare10071194
|View full text |Cite
|
Sign up to set email alerts
|

Coronasomnia in Employees without a Direct Contact with COVID-19 Infected Patients in Their Workplace

Abstract: Background: The aim of this analysis was to explore coronasomnia in second line workers. Methods: Data were collected via in an online questionnaire. Patients with new onset or aggravation of insomnia were defined as cases and those without insomnia as controls. Differences among groups were studied by nonparametric tests; the correlation among variables was assessed using regression, followed by Bonferroni adjustment. Results: There were 377 responders, grouped into 129 cases and 248 controls. Younger age (Od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Important maternal–fetal repercussions result from prenatal anxiety [ 10 ]. Excessive panic would probably worsen the symptoms, leading in some cases to consequences such as coronasomnia [ 4 , 15 ]. This may be linked to preterm birth, fetal growth restriction, and obstetric difficulties and may have long-lasting impacts on a child’s growth and development, either directly or indirectly [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Important maternal–fetal repercussions result from prenatal anxiety [ 10 ]. Excessive panic would probably worsen the symptoms, leading in some cases to consequences such as coronasomnia [ 4 , 15 ]. This may be linked to preterm birth, fetal growth restriction, and obstetric difficulties and may have long-lasting impacts on a child’s growth and development, either directly or indirectly [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Miscarriage due to SARS-CoV-2 infection can happen at 34 weeks [ 37 ]. Therefore, it has been discovered that immunization against COVID-19 is the most effective method for preventing major disease or consequences in pregnant women (and the fetus) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, several years after the HIV/AIDS pandemic had begun back in the 1990s, there was much reluctance in dental professionals toward working with and for PLWHA [ 21 ]. Despite the fact that prophylaxis is available for general infectious diseases and should be known by all healthcare workers [ 22 , 23 , 24 , 25 ], dental professionals may be exposed when working with PLWHA, and the risk of getting infected still exists even today. HIV pre-exposure and post-exposure prophylaxis methods are important when it comes to HIV/AIDS prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is recommended for girls and boys as well. As for the public attitudes and potential hesitant attitudes, several Romanian studies regarding vaccination have shown that a low level or absence of knowledge has determined parents’ decision to not vaccinate their children in general [ 16 , 17 , 18 , 19 ]. It is known and proven that HPV vaccination is an effective tool against several types of cancer, especially cervical cancer.…”
Section: Introductionmentioning
confidence: 99%